Perubahan Kebijakan Luar Negeri Amerika Serikat dalam Mengatasi Imigran Ilegal di Perbatasan Dengan Meksiko - Rahmadhani, Putri; Apriwan, Apriwan; Setyaka, Virtuous (Palito, 2023)
The United States, particularly illegal immigrants from the Mexico border, is the primary destination country for these immigrants. In addressing the threat posed by illegal immigrants, the US implements foreign policy measures. Research aims to explain the factors contributing to these changes and examine the extent of changes in the US foreign policy concerning illegal immigration. The factors and levels of changes are analyzed using the foreign policy change theory developed by Jakob Gustavsson. The factors of change consist of international and domestic factors, encompassing political and economic elements. The levels of change categorized as adjustment changes, program changes, problem/goal changes, and international orientation changes. The research methodology employed is qualitative, utilizing a descriptive analytical approach and relying on secondary data. The international factors within the political realm include increasing criminal activities, while the economic aspect pertains to issues regarding low wages for workers. Domestic factors within the political sphere involve changes in foreign policy resulting from the fulfillment of campaign promises influenced by political parties, and the economic aspect relates to the declining income of the American population, affecting the average income of U.S. citizens. The observed levels of change predominantly fall under program changes and international orientation changes.